Crotonylation versus acetylation in petunia corollas with reduced acetyl‐CoA due to PaACL silencing. Issue 5 (17th October 2022) - Yang, Weiyuan; Li, Xin; Jiang, Guiyun; Long, Yu; Li, Hui; Yu, Shujun; Zhao, Huina; Liu, Juanxu
Abstract: Protein acetylation and crotonylation are important posttranslational modifications of lysine. In animal cells, the correlation of acetylation and crotonylation has been well characterized and the lysines of some proteins are acetylated or crotonylated depending on the relative concentrations of acetyl‐CoA and crotonyl‐CoA. However, in plants, the correlation of acetylation and crotonylation and the effects of the relative intracellular concentrations of crotonyl‐CoA and acetyl‐CoA on protein crotonylation and acetylation are not well known. In our previous study, PaACL silencing changed the content of acetyl‐CoA in petunia ( Petunia hybrida ) corollas, and the effect of PaACL silencing on the global acetylation proteome in petunia was analyzed. In the present study, we found that PaACL silencing did not significantly alter the content of crotonyl‐CoA. We performed a global crotonylation proteome analysis of the corollas of PaACL ‐silenced and control petunia plants; we found that protein crotonylation was closely related to protein acetylation and that proteins with more crotonylation sites often had more acetylation sites. Crotonylated proteins and acetylated proteins were enriched in many common Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. However, PaACL silencing resulted in different KEGG pathway enrichments of proteins with different levels of crotonylation sites and acetylation sites. PaACLB1‐B2 silencing did not led to changes in the opposite direction in crotonylation and acetylation levels at the same lysine site in cytoplasmic proteins, which indicated that cytoplasmic lysine acetylation and crotonylation might not depend on the relative concentrations of acetyl‐CoA and crotonyl‐CoA. Moreover, the global crotonylome and acetylome were weakly positively correlated in the corollas of PaACL ‐silenced and control plants.